Courtship, egg sac construction, and maternal care in Kukulcania hibernalis, with information on the courtship of Misionella mendensis (Araneae, Filistatidae) - Barrantes, Gilbert (2013)
Morphological and behavioural traits place Filistatidae basally within Araneomorphae, although some features, such as their continuing to moult after reaching adulthood, are reminiscent of mygalomorph spiders. This paper describes the courtship behaviour and other aspects of the reproductive biology of Kukulcania hibernalis and Misionella mendensis, and compares this information with that from related species and with Mygalomorphae. K. hibernalis has some unique behaviours during courtship (e.g. male lays threads on female web); other behaviours are probably widespread within Filistatidae (e.g. male uses the tarsi and metatarsi of one of his legs to rub the basal sections of the female's legs and the sides of her cephalothorax). Some other behaviours seem more similar to Mygalomorphae than to those of other, more derived Araneomorphae. These include male construction of a large sperm web, and the positions of male and female facing each other during copulation, with the male holding the female cephalothorax lifted while insertions occur, similar to some mygalomorphs. The adult female K. hibernalis and the first instar spiderlings (outside the eggsac) feed simultaneously on the same prey, but spiderlings are also capable of cooperating during the attack of large prey. The courtship behaviour supports the hypothesis that places Filistatidae basally within Araneomorphae.